CAA2016 : oceans of data : proceedings of the 44th Conference on Computer Applications and Quantitative Methods in Archaeology - Matsumoto, Mieko, 1947-; Uleberg, Espen, (Archaeopress Publishing Ltd, 2018)
A selection of 50 papers presented at CAA2016. Papers are grouped under the following headings: Ontologies and Standards; Field and Laboratory Data Recording and Analysis; Archaeological Information Systems; GIS and Spatial Analysis; 3D and Visualisation; Complex Systems Simulation; Teaching Archaeology in the Digital Age.